Letter (copy) : Purchase of surgical instruments for Spain - Tewson, Vincent
041-0136-001 HVT/FC/144. Secretary's. 24th October, 1936. Mr. W. Schevenels, The International Federation of Trade Unions, 9, Avenue D'orsay, PARIS VIIe. Dear Dr. Schevenels, I am enclosing correspondence which we have received in regard to assisting with the purchase of surgical instruments for Spain. Two representatives of the Office of Propaganda in Catalonia have come to London to set up an Information Bureau and although we have had requests to send a representative to attend a meeting we have, as yet, taken no action. Our contact now with Spain is through the Committee in Madrid and obviously the requirements mentioned in the enclosed correspondence are for Barcelona. In the first place, before taking any action I should be glad to have your comments in regard to the request enclosed and, secondly, will you please let me know if any similar information bureau has been set up in Paris by the Catalonian Government, and what is the reaction of the Spanish government to this Organisation. Yours sincerely, Assistant Secretary. Correspondence. 292/946/41/136